Economic factors affecting financial ratios; Real estate investment trusts case on ISE - (:unkn) unknown (My University, 2012)
The purpose of this study is to analyze the effects of macroeconomic conditions and financial ratios on net profit after tax/equity ratio of the real estate investment trusts (REITs). We selected thirteen real estate investment trusts' firm financial ratios that are included on Istanbul Stock Exchange (ISE) between the years 2007-2010. Findings suggests that total debt /net asset value, total debt/equity, acid-test ratio, net profit after tax/net asset value, net asset value per share/common stock price and Dollar/Turkish Lira currency volatility has significant relation on net profit after tax/equity ratio. Findings of this analysis helps REIT managers forecast on different economic and financial structure conditions in order to optimize their net profit after tax/equity ratio. © 2012 EuroJournals Publishing, Inc.
Keywords: Financial Structure; Real estate investment trusts